2016
DOI: 10.1080/09571736.2016.1172328
|View full text |Cite
|
Sign up to set email alerts
|

Oral corrective feedback: teachers’ concerns and researchers’ orientation

Abstract: Studies on oral corrective feedback have been mainly directed towards cognitive factors. Practical aspects of error correction have been ignored to a large extent. The present study attempted to fill this gap by investigating teachers' practice and beliefs about oral error correction and the priorities they set for themselves and comparing the results with the recent research findings to find the areas of mismatch between the two domains. Seven teachers were observed, each on two occasions, which made 14 class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 61 publications
2
10
0
Order By: Relevance
“…The teacher-trainees in this study were at a double disadvantage as they were only beginning to learn about the profession and had little teaching experience. However, even when teachers see CF as important in promoting L2 development, they often struggle to provide correction, worrying about interrupting the communicative flow, negatively affecting learners’ well-being, or simply not knowing when the right time to correct may be (Basturkmen et al, 2004; Brown, 2009; Roothooft, 2014; Sepehrinia & Mehdizadeh, 2016). The concern for learners’ reaction to CF and confusion about the proper timing of CF was evident in the pre-service teachers’ responses on the beliefs questionnaire when, as a group, they appeared cognizant about the affective factors of CF and could not decide on the phase (immediately, at the end of a lesson, or in a separate lesson) that would render correction most effective.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The teacher-trainees in this study were at a double disadvantage as they were only beginning to learn about the profession and had little teaching experience. However, even when teachers see CF as important in promoting L2 development, they often struggle to provide correction, worrying about interrupting the communicative flow, negatively affecting learners’ well-being, or simply not knowing when the right time to correct may be (Basturkmen et al, 2004; Brown, 2009; Roothooft, 2014; Sepehrinia & Mehdizadeh, 2016). The concern for learners’ reaction to CF and confusion about the proper timing of CF was evident in the pre-service teachers’ responses on the beliefs questionnaire when, as a group, they appeared cognizant about the affective factors of CF and could not decide on the phase (immediately, at the end of a lesson, or in a separate lesson) that would render correction most effective.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study (Rahimi & Zhang, 2015), however, suggests that experienced teachers view CF more positively (90%) than novice teachers (75%) do. Second, teachers may feel that providing CF during a student’s attempt to communicate may unduly interrupt the communicative flow (Brown, 2009; Roothooft, 2014; Sepehrinia & Mehdizadeh, 2016); thus, only those errors that inhibit understanding need to be addressed (Jean & Simard, 2011; Roothooft, 2014). To avoid the perceived ‘humiliating’ (Kamiya, 2014) nature of explicit correction, some teachers may gravitate towards recasts when CF is needed (Bell, 2005; Rahimi & Zhang, 2015), seeing them as a non-intruding yet face-saving and target-providing solution (Lee, 2013; Yoshida, 2010); experienced teachers, however, are more likely to vary the types of CF they use (Junqueira & Kim, 2013; Rahimi & Zhang, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, the tendency is leading researchers to focus on the social interactionist perspective of OCF (Althobaiti, 2014;Ayedh & Khaled, 2011;Ellis, 2009;Martinez Agudo, 2012;Roothooft, 2014;Sepehrinia & Mehdizadeh, 2016, Wass et al, 2018 in order to fulfil the need of taking into consideration the affective component of the EFL teaching and learning processes. Thus, this research goes in line with Ellis's (2009) assertion that corrective feedback is a highly complex instructional and interactive phenomenon that manifests cognitive, social and psychological dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…
Recent research has shown that little attention has been paid to teachers' views regarding giving oral corrective feedback (Sepehrinia & Mehdizadeh, 2016). To fill this gap, this empirical study investigates the beliefs of Taif University's teachers of English as a Foreign Language (EFL) about their feedback practices and their perception of the impact that these practices have on students' performance.
…”
mentioning
confidence: 99%